Walking after spinal cord injury. Goal or wish? - Subbarao, J. V. (1991)
Less than a third of patients walk again after a spinal cord injury, whereas every one of them wants to try. Residual function, energy expenditure, the extent of orthotic support needed, and patient motivation will determine the outcome. Functional electrical stimulation and other new orthotic designs have not notably increased the number of persons able to walk after a spinal injury. Rehabilitation professionals can use patient education, illustrating relearning to walk with examples of infants' and toddlers' progress, to assist patients in understanding their abilities and limitations. The final decision on ambulation and orthotic prescriptions can be made in stages after a patient adjusts to a wheelchair-independent level.